Li3SbO4 Lithium-Ion Battery Material: Defects, Lithium Ion Diffusion and Tetravalent Dopants - Kuganathan, N.; Kordatos, A.; Anurakavan, S.; Iyngaran, P.; Chroneos, A. (University of Jaffna, 2019)
Lithium antimony oxide, Li3SbO4, is a candidate anode material for rechargeable lithium ion batteries. Static atomistic scale simulations based on the classical pair potentials are employed to provide insights into the defect chemistry, doping behaviour and lithium diffusion paths in Li3SbO4. Here we show that, Li Frenkel is the dominant intrinsic defect process and the activation energy of Li diffusion is very low (0.21eV) suggesting that very high Li conduction is expected in this material. In particular, long range lithium diffusion paths via vacancy mechanism were constructed and it is confirmed that the lowest activation energy migration path is along the bc-axis plane with a zig-zag pattern. The calculations further suggest that cation anti-site defects, in which Li and Sb exchange their atomic positions, would not be observed with significant intrinsic concentration at operating temperatures. Subvalent doping by Si on the Sb site is energetically favourable suggesting that this efficient way to increase the Li content in Li3SbO4 should be stimulated experimentally. The electronic structure calculations based on the density functional theory (DFT) show that introduction of tetravalent dopants will not alter the band-gap significantly.
Keywords: :Li3SbO4; Defects; Li diffusion; Dopants